2005
DOI: 10.1523/jneurosci.4186-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Multisynaptic Inputs from Prefrontal Cortex to Primary Motor Cortex as Revealed by Retrograde Transneuronal Transport of Rabies Virus

Abstract: The organization of multisynaptic projections from the prefrontal cortex to the primary motor cortex (MI) was examined in macaque monkeys by retrograde transneuronal transport of rabies virus. In the first series of experiments, the virus was injected into the MI forelimb region, and the time-dependent distribution patterns of transsynaptic labeling were analyzed in the frontal lobe with various survivals (2-4 d). Two days after the viral injection, neuronal labeling emerged in the caudal aspects of the nonpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 60 publications
3
68
0
Order By: Relevance
“…As neither area 46v nor SEF directly projects to MT or V4, neuronal labeling in these areas at the 3 d postinjection period verifies the trans-synaptic transport of rabies virus. Furthermore, the internal control tested in our laboratory (Miyachi et al, 2005) and the consistency of labeling patterns in V1 with previous data Ninomiya et al, 2011) indicate that neuronal labeling in area 46v and SEF is ascribable to the second-order labeling occurring at the 3 d postinjection period. However, there may exist the possibility that some weak disynaptic connections remain unlabeled with the 3 d survival time.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As neither area 46v nor SEF directly projects to MT or V4, neuronal labeling in these areas at the 3 d postinjection period verifies the trans-synaptic transport of rabies virus. Furthermore, the internal control tested in our laboratory (Miyachi et al, 2005) and the consistency of labeling patterns in V1 with previous data Ninomiya et al, 2011) indicate that neuronal labeling in area 46v and SEF is ascribable to the second-order labeling occurring at the 3 d postinjection period. However, there may exist the possibility that some weak disynaptic connections remain unlabeled with the 3 d survival time.…”
Section: Discussionsupporting
confidence: 81%
“…This strain was the same as that introduced by Ugolini (1995) and Kelly and Strick (2000) to demonstrate specific retrograde trans-synaptic transport of the virus. The rate of retrograde transport for the viral batch used in this study was calibrated in our previous study (Miyachi et al, 2005). By evaluating transneuronal labeling in the cortico-basal and cerebro-cerebellar loop circuits, we concluded that it takes ϳ2 d for first-order neuron labeling and one additional day per one synapse for subsequent transneuronal labeling.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent evidence suggests that the anterior cingulate cortex can produce signals specific of the first distinct reward, which marks the end of exploration (Quilodran et al, 2008). By directly and indirectly providing directions for the operational states of dlPFC as well as for the dorsal premotor areas (Miyachi et al, 2005;Tanji and Hoshi, 2008), it is likely that such signals supported the implementation of the desired action representation in the bimanual trials. Indeed, evidence in macaques during reaching indicates that arm selection involves neural processes in the dorsal premotor and supplementary motor areas Tanji, 2000, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although spread of induced current to adjacent brain areas is possible, studies using a similar coil have reported an effective resolution of approximately a centimeter Walsh and Cowey, 2000) and the effect of dMFC TMS can be distinguished from that of adjacent dorsal premotor cortex (Rushworth et al, 2002;Kennerley et al, 2004b). Although pre-SMA is not directly interconnected with M1 or spinal cord (Luppino et al, 1993;He et al, 1995), it contains neurons that respond when hand movements are made (Fuji et al, 2001) and it is interconnected with M1 through a multisynaptic pathway (Miyachi et al, 2005). It is realistic to assume that dMFC TMS could impact on M1 activity via a multisynaptic pathway.…”
Section: Discussionmentioning
confidence: 99%